Short total synthesis of (+)-cryptocarya diacetate - Gurjar, Mukund K.; Raghupathi, Neelarapu; Chorghade, Mukund S. (Heterocycles, 2009)
A short synthesis of (+)-cryptocarya diacetate was achieved by employing three component linchpin coupling, diastereoselective reduction of beta-hydroxyketone, and Z-selective HWE reaction as key transformations.
Keywords: Brook Rearrangement; cryptocarya diacetate; Diastereoselective Reduction; Horner-Wadswarth-Emmons Reaction; Linchpin coupling